MEWFM 2022
DOI: 10.5742/mewfm.2022.9525098
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Use of Contraceptive Methods for Family Planning among Married Women of Rawalpindi [urban]

Abstract: Qualitative data from a survey of married women living in urban areas of Rawalpindi are presented here in an effort to better understand their views on contraceptive techniques and the factors that impact their use. A purposeful selection strategy was used to choose participants, and only married women of childbearing age were eligible to participate. In total, 12 focus groups were held in the urban region of Rawalpindi. Some modern contraceptive methods were known to the majority, but overall use was extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Therefore, there were deliberate efforts by signi cant others (elders) who were antagonizing contraception programs, saying it will kill their families and as such, encouraged their people to produce many children who will replace the lost family members and be a source of security, free labor, and wealth. This nding concurs with several studies which revealed that cultural and religious norms including social stigma were signi cant factors affecting contraceptive use (Lateef et al, 2022, Singh et al, 2022, Noormal et al, 2022, Casey et al, 2020, Yland et al, 2020. This has implications for public health as culture take precedence to the health of women and girls.…”
Section: Dynamics Of Contraceptive Usesupporting
confidence: 90%
“…Therefore, there were deliberate efforts by signi cant others (elders) who were antagonizing contraception programs, saying it will kill their families and as such, encouraged their people to produce many children who will replace the lost family members and be a source of security, free labor, and wealth. This nding concurs with several studies which revealed that cultural and religious norms including social stigma were signi cant factors affecting contraceptive use (Lateef et al, 2022, Singh et al, 2022, Noormal et al, 2022, Casey et al, 2020, Yland et al, 2020. This has implications for public health as culture take precedence to the health of women and girls.…”
Section: Dynamics Of Contraceptive Usesupporting
confidence: 90%
“…In other words, since the complete opening of the national two-child policy in 2016, the birth population in China has not increased but has decreased. e sharp population decline is a very terrible trend [31]. e Total Fertility Rate (TFR) of China from 1970 to 2020 is plotted in Figure 6.…”
Section: Fertility Policy and Fertility Rate Changesmentioning
confidence: 99%
“…The population under study came from a community where sensitization on contraception was not a government priority. It is clear that when people do not know about a service or have limited knowledge about it, they would not seek to use the service [37]. The participants in this study reported that contraceptive information is not widely known or disseminated in their settlements.…”
Section: Plos Onementioning
confidence: 83%